Moral Conflict and The Tragedy of Female Consciousness in Leo Tolstoy’s - Rakhmatullaeva Komila Normamat kizi (International Scientific and Current Research Conferences, 2025)
This article examines the portrayal of female consciousness in Leo Tolstoy’s Anna Karenina through the lenses of morality, freedom, and psychological realism. The novel’s central figure, Anna, embodies the conflict between individual passion and social morality, revealing the limitations of nineteenth-century patriarchal ethics. Tolstoy’s moral universe contrasts Anna’s spiritual disintegration with the inner harmony achieved by Kitty and Dolly, illustrating his complex vision of womanhood. Using hermeneutic, psychoanalytic, and ethical approaches, the study explores the dialectic of freedom and duty in female identity, emphasizing Tolstoy’s conviction that true liberation can only arise from moral integrity and self-awareness. Ultimately, the novel presents a timeless meditation on the human condition: the tragic impossibility of reconciling love, freedom, and social conscience.